Defects-Induced Hot Spots in TATB - Zhonghua Yan; Chuanchao Zhang; Hongwei Yan; Zhijie Li; Li Li; Ming Huang; Bisheng Tan; Xiaodong Yuan (Advances in Condensed Matter Physics)
We investigate the interaction between the laser and energetic materials with different defects. The three-dimensional models of triaminotrinitrobenzene (TATB) explosives containing spherical pores, craters, and cracks are established, respectively. The laser ignition process of TATB is simulated with three-dimensional finite difference time domain (3D-FDTD) method to study the electromagnetic field distribution surrounding these defects with 355 nm laser incidence. It indicates that the larger defects in the TATB energetic materials have the stronger electric field modulations to initial incident laser for all the three defects, which is easier to lead to the generation of hot spots. Furthermore, TATB materials with spherical pore defects and crater defects are easier to form hot spots than those with narrow crack defects.